1D Anderson model revisited: Band center anomaly for correlated disorder - Herrera-González, I.F.; Izrailev, F.M.; Makarov, N.M.; Tessieri, L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
We study the band-center anomaly in the one-dimensional Anderson model with the disorder characterized by short-range positive correlations. Using the Hamiltonian map approach, we obtain analytical expressions for the localization length and the invariant measure of the phase variable. The analytical expressions are complemented by numerical data.